Literatura, memória e identidade no Tocantins: Territorialidade Tocantinense imaginada no Romance “Serra dos Pilões - Jagunços e Tropeiros”, de Moura Lima. - Silva., Denize Passos da (2022)
The following research presents the narrative of Serra dos Pilões Jagunços e Tropeiros romance written by Moura Lima from an interdisciplinary construction. The analysis began with the following question: at what extend does the regionalist romance by Moura Lima contribute to the construction of a Tocantinense territory? With these divisions, the aim was to construct a dialogue between History and Literature. We used White (1994, 1995) and Frye (1957) as theoretical supports for doing it. We presented the social insertion of the author and for analyzing it, we used Bourdieu (2007). We studied Ricouer (1997, 2003, and 2010) for the perception of memory topic in the construction of the narrative. We also presented in the romance the elements that we understand as constituters of imaginative territoriality of Tocantins: sertanejos’ language figured by Mora Lima and we related the construction of tragic heroes in the oeuvre to some extend with the tragic hero suggested by Aristotle (384-322 B.C) and Frye (1957). We questioned the figuration of manners in the romance from Thompson (1998). We analyzed in it the presence of Politics and History as emblematic aspects of a territorial construction and some aspects of the figuration as a memory file of northern Goiás from the 1910s. This research reveals the hints of an imaginative construction of a Tocantins territory. For that, we presented the narrative through the immersion of Mora Lima in his age framework senses. We defend the idea that Serra dos Pilões romance is metaphorical in its structure, a territorial metaphor.